Serological evidence of Toxoplasma gondii infection as potential risk for the development of lepromatous leprosy in an endemic area for both neglected tropical diseases in Brazil - Luciana Regina Pereira Oliveira; Lívia Mattos Martins; Rebeka da Conceição Souza; Yuri Scheidegger de Castro; Letícia Silva Nascimento; Juliana Azevedo da Silva; Edilbert Pellegrini Nahn Junior; Wilmar Dias da Silva; Alba Lucínia Peixoto-Rangel (BMC, 2020)
Abstract Background Mycobacterium leprae and Toxoplasma gondii infections are both neglected tropical diseases highly prevalent in Brazil. Infection with certain parasite species can significantly alter susceptibility to other important pathogens, and/or influence the development of pathology. Here we investigated the possible influence of M. leprae/T. gondii co-parasitism on the manifestation of leprosy and its clinical forms. Methods Participants (n = 291) were recruited in Campos dos Goytacazes city, Rio de Janeiro state, southeast Brazil, from August 2015 to December 2019 and clinically diagnosed for leprosy. Participants were selected based on the presence (patients) or absence (healthy controls) of the leprosy disease. Contacts of patients were also recruited for this study. Serum samples from patients (n = 199) with leprosy, contacts (n = 40) and healthy controls (n = 52) were investigated for levels of IgM and IgG anti-phenolic glycolipid-1 (PGL-1) by ELISA. Additionally, IgG antibody against soluble Toxoplasma antigen (STAg) was measured in sera samples from leprosy patients, contacts and healthy controls for Toxoplasma gondii serology by ELISA. Anti-PGL-1 IgG and IgM levels were compared using one-way ANOVA Kruskal-Wallis or Mann-Whitney, while Spearman test was used to correlate levels of IgG anti-STAg and IgM/IgG anti-PGL-1 from seropositive and seronegative individuals for T. gondii infection. The risk of T. gondii infection for leprosy disease was assessed using Fisher's test. Results Levels of IgM anti-PGL-1 antibodies were significantly higher in multibacillary (MB) patients compared to paucibacillary (PB) patients (P = 0.0068). Higher IgM and IgG levels anti-PGL-1 were detected in patients with the lepromatous forms. The serologic prevalence for T. gondii infection was 74.9%. We detected increased anti-STAg antibody levels in leprosy patients (79.4%), reaching 88.8% within those with lepromatous form of this disease. The leprosy risk increase in T. gondii seropositive individuals was two-fold (odds ratio [OR] = 2.055; 95% confidence intervals [95% CI]: 1.18-3.51) higher than those seronegative, and considering the lepromatous leprosy risk this increase was even dramatic (OR = 4.33; 95% CI: 1.76-9.69) in T. gondii seropositive individuals. Moreover the leprosy risk in T. gondii seropositive individuals was weakly correlated to the levels of IgG anti-STAg and IgM/IgG anti-PGL-1. Conclusions Altogether, our results suggest that T. gondii infection may exert immunomodulatory properties that influence to the susceptibility of leprosy, mainly on its more severe clinical form. A better understanding of parasite immunomodulation can ultimately contribute to the development of medical applications.